ChemInform Abstract: Base Initiated Aromatization/C—O Bond Formation: A New Entry to O‐Pyrazole Polyfluoroarylated Ethers. Issue 16 (April 2015) - Tang, Xiangyang; Chang, Jing; Liu, Cuibo; Zhang, Bin
Abstract In addition to the preparation of O‐pyrazole polyfluoroarylated ethers the method is also applicable to the synthesis of the corresponding isoxazole derivatives.